Determining the recommended dose of pacritinib: results from the PAC203 dose-finding trial in advanced myelofibrosis - Gerds, AT; Savona, MR; Scott, BL; Talpaz, M; Egyed, M; Harrison, CN; Yacoub, A; Vannucchi, A; Mead, AJ; Kiladjian, J-J; O'Sullivan, J; García-Gutiérrez, V; et al. (American Society of Hematology, 2020)
PAC203 is a randomized dose-finding study of pacritinib, an oral JAK2/IRAK1 inhibitor, in patients with advanced myelofibrosis who are intolerant of or resistant to ruxolitinib. Patients were randomized 1:1:1 to pacritinib 100 mg once per day, 100 mg twice per day, or 200 mg twice per day. Enhanced eligibility criteria, monitoring, and dose modifications were implemented to mitigate risk of cardiac and hemorrhagic events. Efficacy was based on ≥35% spleen volume response (SVR) and ≥50% reduction in the 7-component total symptom score (TSS) through week 24. Of 161 patients, 73% were intolerant of and 76% had become resistant to ruxolitinib; 50% met criteria for both. Severe thrombocytopenia (platelet count <50 × 103/μL) was present in 44%. SVR rates were highest with 200 mg twice per day (100 mg once per day, 0%; 100 mg twice per day, 1.8%; 200 mg twice per day, 9.3%), particularly among patients with baseline platelet counts <50 × 103/μL (17%; 4 of 24). Although TSS response rate was similar across doses (100 mg once per day, 7.7%; 100 mg twice per day, 7.3%; 200 mg twice per day, 7.4%), median percent reduction in TSS suggested a dose-response relationship (–3%, −16%, and −27%, respectively). Pharmacokinetic and pharmacodynamic modeling based on all available data showed greatest SVR and TSS reduction at 200 mg twice per day compared with lower doses. Common adverse events were gastrointestinal events, thrombocytopenia, and anemia. There was no excess of grade ≥3 hemorrhagic or cardiac events at 200 mg twice per day. Pacritinib 200 mg twice per day demonstrated clinical activity and an acceptable safety profile and was selected as the recommended dose for a pivotal phase 3 study in patients with myelofibrosis and severe thrombocytopenia. This trial was registered at www.clinicaltrials.gov as #NCT03165734.